(untitled) (Transactions of the Association of European Schools of Planning, 2021)
Social innovation is recurrently positioned as an important collaborative element in helping cities to transition and address human needs and societal challenges to enhance the health, wellbeing, and welfare of citizens. To address a call for more sector-specific research on the spatiality of social innovation, and also further understanding of the process dimension of social innovation, this article presents a conceptual framework of the process of social innovation. By combining social innovation insight from process theories and urban spaces discourse the article indicates that of social innovation in the co-production of space can be grouped into four major processes: 1) Identification of human needs or societal challenges to sustainable development; 2) Development of social relations in systems or structures; 3) Provision of opportunity for social empowerment; 4) Reflection of socio-spatial development practice. Applying this framework, the article examines how productive green infrastructure emerges in the urban landscape as a Place of Social Innovation (POSI).